2014
DOI: 10.1016/j.immuni.2014.01.003
|View full text |Cite
|
Sign up to set email alerts
|

The Cytokine IL-22 Promotes Pathogen Colonization by Suppressing Related Commensal Bacteria

Abstract: Summary Interleukin-22 (IL-22) is highly induced in response to infections with a variety of pathogens and its main functions are considered to be tissue repair and host defense at mucosal surfaces. Here we show that IL-22 has a previously undiscovered role during infection in that its expression suppresses the intestinal microbiota and enhances the colonization of a pathogen. IL-22 induced the expression of antimicrobial proteins, including lipocalin-2 and calprotectin, which sequester metal ions from microbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
246
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 259 publications
(258 citation statements)
references
References 54 publications
12
246
0
Order By: Relevance
“…We first tested the ability of WT or SPI-6-deficient strains to kill representative commensals of the gut microbiota in vitro. Using the conditions described above, we show that S. Typhimurium kills K. oxytoca and Klebsiella variicola in a SPI-6-dependent manner, but not Enterobacter cloacae or the E. coli JB2 mouse commensal strain (28) (Fig. 2B).…”
Section: S Typhimurium T6ss Kills Microbiota Members and Is Enhanced Bymentioning
confidence: 85%
See 3 more Smart Citations
“…We first tested the ability of WT or SPI-6-deficient strains to kill representative commensals of the gut microbiota in vitro. Using the conditions described above, we show that S. Typhimurium kills K. oxytoca and Klebsiella variicola in a SPI-6-dependent manner, but not Enterobacter cloacae or the E. coli JB2 mouse commensal strain (28) (Fig. 2B).…”
Section: S Typhimurium T6ss Kills Microbiota Members and Is Enhanced Bymentioning
confidence: 85%
“…Previous studies on the mechanisms of S. Typhimurium colonization of the mouse gut have shown that Salmonella exploits intestinal inflammation to compete with the resident microbiota and to thrive in the inflamed gut (28)(29)(30)(31)(32). All these previous studies have been performed in mice that have been pretreated with an antibiotic (e.g., streptomycin) that perturbs the indigenous microbiota.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is possible that the liberation of antibacterial linoleic acid is primarily targeted against other bacteria thereby conferring growth advantage to S. aureus. Such a mechanism has been proposed for Salmonella where the bacteria induce the production of antimicrobial proteins in the intestine that in turn altered the normal microbiota facilitating infection with the pathogen [90] . Successful pathogens subvert host defense mechanisms that normally control infection.…”
Section: Bacterial Mechanisms That Manipulate Host-derived Lipidsmentioning
confidence: 99%